2014
DOI: 10.1155/2014/485743
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the Lack of CD73 and Prostatic Acid Phosphatase in the Lymphoid Organs

Abstract: CD73, ecto-5′-nucleotidase, is the key enzyme catalyzing the conversion of extracellular AMP to adenosine that controls vascular permeability and immunosuppression. Also prostatic acid phosphatase (PAP) possesses ecto-5′-nucleotidase/AMPase activity and is present in leukocytes. However, its role related to immune system is unknown. Therefore, we analyzed enzymatic activities and leukocyte subtypes of CD73 and PAP knockouts and generated CD73/PAP double knockout mice to elucidate the contribution of CD73 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Despite its canonical association with the prostate gland, recent studies have indicated that TM-PAP and/or the secreted PAP isoform function as significant ectonucleotidases in multiple tissues and cell types, including saliva (Araujo et al, 2014), dorsal root ganglion neurons that mediate nociception (Street et al, 2011;Zylka et al, 2008), and normal T lymphocytes (Yegutkin et al, 2014). Up-regulated PAP is also used as a biomarker of prostate cancer (Hakalahti et al, 1993), and our observations suggest the possibility that it may also be a marker for some subtypes of leukemias.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Despite its canonical association with the prostate gland, recent studies have indicated that TM-PAP and/or the secreted PAP isoform function as significant ectonucleotidases in multiple tissues and cell types, including saliva (Araujo et al, 2014), dorsal root ganglion neurons that mediate nociception (Street et al, 2011;Zylka et al, 2008), and normal T lymphocytes (Yegutkin et al, 2014). Up-regulated PAP is also used as a biomarker of prostate cancer (Hakalahti et al, 1993), and our observations suggest the possibility that it may also be a marker for some subtypes of leukemias.…”
Section: Discussionmentioning
confidence: 66%
“…Multiple ACPP splice variants yield a secreted PAP isoform and another with a transmembrane anchor (TM-PAP). Recent studies have indicated that TM-PAP mRNA and enzyme activity is expressed in normal murine and human lymphoid tissues and different T-cell subsets (Quintero et al, 2007;Yegutkin et al, 2014). Notably, inclusion of 10 mM L-tartrate, as a low affinity but high-efficacy inhibitor of PAP isozymes, markedly (∼80%) attenuated the robust «-AMP → «-ADO metabolism by the RIP1-deficient Jurkat cells (Fig.…”
Section: Tnfa-induction Of Necroptosis or Extrinsic Apoptosismentioning
confidence: 87%
See 1 more Smart Citation
“…Traffic of lymphocytes between blood and tissues is essential for propagation of inflammation and purinergic signaling plays an important role in this process through conditioning kinetics of lymphocytes (Henttinen et al, 2003;Yegutkin et al, 2014). Extravasation of leukocytes to target tissue consists of following steps: temporal adhesion of lymphocytes to vascular endothelium, rolling of cells along endothelium, activation resulting in holding of the cells and subsequent transmigration into tissue (Springer, 1994).…”
Section: Ado and Atp Control The Rolling Of Lymphocytes During Inflammentioning
confidence: 99%
“…Interestingly, both retinoids ( Mucida et al, 2007 ) and ADO ( Ohta and Sitkovsky, 2014 ) promote the TGF-β-dependent development of T reg cells in the periphery. In CD73/prostatic acid phosphatase double knock out mice, where the extracellular ADO levels are low, the tT reg cell production was found to be impaired ( Yegutkin et al, 2014 ) indicating the involvement of ADO also in the tT reg cell differentiation.…”
Section: Effect Of Adenosine On the T Cell Developmentmentioning
confidence: 99%